A new species of Solanum subg. Leptostemonum (Solanaceae) from the southern Espinhaço Range, Minas Gerais, Brazil - Agra, Maria De Fátima; Stehmann, João Renato (Phytotaxa, 2016)
Solanum mellobarretoi, a new species of Solanum subg. Leptostemonum (Solanaceae), is described and illustrated. It is endemic to Brazil and restricted to the southern Espinhaço Range in the State of Minas Gerais, southeastern Brazil. Solanum mellobarretoi is morphologically related to S. leptostachys Dunal, from which it differs by its irregularly lobed lanceolate to ovate-lanceolate leaves, irregularly lobed, ovate to lanceolate calyx lobes, larger flowers, and pentagonal rotate corolla with cuspidate lobes. Although known in other groups of Solanum, the explosive seed dispersal mechanism found in this species is described here for the first time for the spiny solanums. The affinities with S. leptostachys, geographic distribution, ecology and conservation status of S. mellobarretoi are discussed.